The Drosophila fragile X mental retardation protein modulates the neuronal cytoskeleton to limit dendritic arborization. - Li, H.; Gavis, E.R. (Development, 2022)
Dendritic arbor development is a complex, highly regulated process. Post-transcriptional regulation mediated by RNA-binding proteins plays an important role in neuronal dendrite morphogenesis by delivering on-site, on-demand protein synthesis. Here, we show how the Drosophila fragile X mental retardation protein (FMRP), a conserved RNA-binding protein, limits dendrite branching to ensure proper neuronal function during larval sensory neuron development. FMRP knockdown causes increased dendritic terminal branch growth and a resulting overelaboration defect due, in part, to altered microtubule stability and dynamics. FMRP also controls dendrite outgrowth by regulating the Drosophila profilin homolog chickadee (chic). FMRP colocalizes with chic mRNA in dendritic granules and regulates its dendritic localization and protein expression. Whereas RNA-binding domains KH1 and KH2 are both crucial for FMRP-mediated dendritic regulation, KH2 specifically is required for FMRP granule formation and chic mRNA association, suggesting a link between dendritic FMRP granules and FMRP function in dendrite elaboration. Our studies implicate FMRP-mediated modulation of both the neuronal microtubule and actin cytoskeletons in multidendritic neuronal architecture, and provide molecular insight into FMRP granule formation and its relevance to FMRP function in dendritic patterning.